Strand 1: Networked Professional Development for Library and Information Staff: A Constructivist Approach - Levy, Philippa (Proceedings of the International Conference on Networked Learning, 1998)
The Internet is a rich technological, information and communication environment which as yet is relatively little explored as a space for learning based on constructivist principles. This paper describes an Internet-based professional development course for library and information staff which was offered in 1997-8 by NetLinkS, a training and awareness project funded by the HEFCE ’Electronic Libraries’ programme. The experiential and collaborative design of the course was informed by the principles of constructivism, and the paper raises some questions for evaluation of the pedagogic model, highlighting in particular the issue of provision of appropriate support and challenge for participants to become skilled in the practice of independent networked learning. The paper suggests that whilst the concept of becoming skilled in online learning is a theme running through much CSCL work, contextualised pedagogic models for active networked learning - which adopt an integrated approach to learner support in the design and sequencing of activities, the use of information resources and support, approaches to tutoring, and technological design, facilities and help - are as yet little discussed. It is hoped that case study research into the implementation of this course will help illuminate the wider question of how to embed support for ’learning to learn’ into the overall design and facilitation of constructivist, networked learning environments.